2009
DOI: 10.3748/wjg.15.1113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different periods of renal ischemia on liver as a remote organ

Abstract: AIM:To assess the hepatic changes after induction of different periods of renal ischemia. METHODS:Rats were subjected to either sham operation or ischemia (30, 45 and 60 min) followed by 60 min reperfusion. Liver and renal functional indices were measured. Hepatic glutathione (GSH) and ferric reducing antioxidant power levels and the concentration of interleukin (IL)-10 and tumor necrosis factor (TNF-α) were evaluated. Portions of liver and kidney tissues were fixed for histological evaluation. RESULTS:Forty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 16 publications
8
46
0
Order By: Relevance
“…These results are in line with Mount et al (2012) and Chen et al (2012). Furthermore, Kadkhodaee et al (2009) reported that the rise of renal injury markers was dependent on the renal ischemia time, and Jung et al (2009) found the increase in renal injury markers reached the peak 48 hours after the renal I/R injury. On the other hand, Vinodini et al (2009) reported no change in serum urea level after renal I/R; this controversy is due to protocol differences as the rats underwent unilateral I/R, and the reperfusion period was only 90 minutes.…”
Section: Discussionsupporting
confidence: 79%
“…These results are in line with Mount et al (2012) and Chen et al (2012). Furthermore, Kadkhodaee et al (2009) reported that the rise of renal injury markers was dependent on the renal ischemia time, and Jung et al (2009) found the increase in renal injury markers reached the peak 48 hours after the renal I/R injury. On the other hand, Vinodini et al (2009) reported no change in serum urea level after renal I/R; this controversy is due to protocol differences as the rats underwent unilateral I/R, and the reperfusion period was only 90 minutes.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies reported that renal IR could disturb liver function and morphology [9,10]. Kadkhodaee et al suggested that a minimum of 45 minutes ischemia period is necessary to produce the liver damage as a remote organ [10]. Wang et al showed that 1 hour ischemia and 4 or 8 hours reperfusion of the kidney increased the serum ALT and AST which seemed to be due to the hepatic cell membrane damage [9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that renal IR could disturb liver function and morphology [9,10]. Kadkhodaee et al suggested that a minimum of 45 minutes ischemia period is necessary to produce the liver damage as a remote organ [10].…”
Section: Discussionmentioning
confidence: 99%
“…functional derangements and cell death ultimately [9]. This complex pathophysiology resulting from a number of contributing factors, so it is difficult to achieve effective treatment or protection by targeting only individual mediators or mechanisms despite the efforts made to deal with this problem [10].…”
mentioning
confidence: 99%
“…The increasing mortality rate in cases with acute renal injury necessitates designing strategies to assess the effect of renal injury on distant organs [11]. Therefore, several studies [8,[1][2][3][4][5][6][7][8][9][10][11][12][13][14] tried to protect liver from remote injury induced by renal IRI for the prevention and attenuation of acute renal injury related morbidity.…”
mentioning
confidence: 99%